TEOLOGI RAHMAT DENGAN PARADIGMA KEBEBASAN - Adrianus Sunarko (Jurnal Orientasi Baru, 2017)
Theological reflection on grace has a long history. Disput between Augustine and Pelagius on grace has been very well known. In modern times, controversy about grace was raised in the dispute between the dominicans (Thomism) and the Jesuits (Molinism). Learning from weaknesses in those debates, a theological reflection with the 'liberty' paradigm affirms that grace must be understood as nothing other than Godself in action and relation to human beings. Gratia increata should not be separated from gratia creata. Grace is given not only because of human sin, but because of an essence that longs for fulfillment. The working power of grace is not an absolute one as not to leave space for human freedom. Accordingly, grace should not be understood as merely an inward thing. The historical aspect of grace should not be ignored.